How information complexity influences pre-service teachers’ noticing of first graders’ number sense: an experimental study - Wirth, Simone; Philipp, Kathleen; Streit, Christine; Friesen, Marita (ZDM, 2025)
Assessment for learning is mostly informal in first grade and requires teachers to notice children’s mathematical thinking during instruction, attending to relevant and disregarding less relevant information. This study investigated the role of information complexity in vignette-based classroom situations for pre-service teachers’ noticing and addressed the following question: How is pre-service teachers’ attending to, interpreting, and shaping of information affected by different levels of information complexity? Pre-service teachers were provided more and less relevant information when assessing first graders’ number sense in four text-image vignettes including student solutions, teacher notes and student-teacher dialogues in an online questionnaire. The $N=$172 participants were randomly assigned to three experimental conditions with varied information complexity, e.g., through highlighting relevant information. The Restricted Focus Viewer was used to track pre-service teachers’ information gathering via computer mouse movements and to collect corresponding process data. Written assessments of children’s number sense were collected as product data of the participants’ information gathering. Both types of data were analysed to draw inferences about pre-service teachers’ cognitive processes assumed to underly their noticing in the provided assessment situations. Our findings indicate that pre-service teachers are better enabled to selectively attend to relevant information and to engage in shaping when the complexity of information is reduced. In terms of interpreting children’s number sense, no significant effect of different information complexity could be found. However, pre-service teachers were more likely to focus on interpreting children’s mathematical thinking and to disregard more generic characteristics, such as diligence.
Online veröffentlicht: 13. August 2025
Gesehen am 12.01.2026